Potential Antianemia Activity of Cokelat Seaweed Extract (Sargassum Duplicatum) on Mencit (Mus Musculus) Injured With NaNO2 - Umpain, Agnes Nesa; Lukman Hardia; Ratih Arum Astuti (Sean Institute, 2025)
Seaweed is one of the leading commodities that is rich in nutrients and bioactive compounds that have potential for human health. The content contained in brown seaweed can be used as a therapy in increasing hemoglobin levels in anemia problems. The purpose of this study was to see the potential antianemia activity of brown seaweed extract (Sargassum duplicatum) against white mice (Mus musculus) and what dose can increase hemoglobin levels in mice. This research method is an experimental method with the Hb stick method carried out on 20 white mice, which were divided into 5 groups, namely the positive control group (blood supplement tablets), negative control group NaCMC 1%, treatment group 1 dose of 21 mg / kgBB, treatment group 2 dose 42 mg / kgBB, and treatment group 3 doisis 84 mg / kgBB. Testing the potential antianemia activity of brown seaweed was carried out on mice that had been induced with NaNo 2and then given a dose of extract treatment. The data were analyzed statistically using paired-sample t-test analysis to analyze the effectiveness of the treatment indicated by the difference in the average before and average after treatment. The results of the study Hemoglobin (Hb) g/dl levels on day 1 to day 15 showed a very significant increase in hemoglobin where the parameters of the dose group were close to the normal condition of the positive control group (blood supplement tablets), namely group 3 dose of 84 mg/KgBB, so it can be concluded that brown seaweed extract (Sargassum duplicatum) in group 3 dose of 84 mg/KgBB has potential antianemia activity comparable to the positive control dose (blood supplement tablets).